PENGARUH ANTIMITOSIS EKSTRAK Achyranthes Aspera Linn PADA PEMBELAHAN SEL EMBRIO (CLEAVAGE) - Wurlina Wurlina (The East Java Biological Society, 2006)
To study the antimitotic effect of an extract of the leaf Achyranthes asapera Linn on embryonal cleavage rats (Rattus norwegicus). Rats ova were fertilized in vitro, and thes suitable zygote and embryo were selected to use as samples, which were divided into 5 groups. Each group comprised 80 ova/embryo. Those groups were: group 1. ova for fertilization, group 2. zygote, group 3. 2 cell embryo, group 4. 4 cell embryo and group 5. 8 cell embryo. Each group was divided into 4 treatmens, each of which consisted of 20 ova/ embryos. The treatments were as follows: control treatment receiving TCM 199 media, and treatment 1, 2 and 3 receiving Achyranthes aspera Linn alkaloid of 20, 30, and 40 ppm respectively. Observation to embryonal cleavage and development was out 12 and 24 hours after treatment. Concluded from the results that the administration of Achyranthes aspera Linn as much as 30 ppm in vitro could 1) inhibits fertilization zygote and 2, 4, and 8 cell embryonal cleavage, growth and development 2) induced zygote and embryonal membrane recruitment and blastomere degeneration and 3) inhibits zygote and embryonal mitotic cleavage at metaphase stage.